Duration of disease does not equally influence all aspects of quality of life in Parkinson's disease. (June 2016) - Benge, Jared F.; Kekecs, Zoltán; Encarnacion, Elmyra; Ainslie, Melissa; Herff, Christina; Elkins, Gary; Herath, Priyantha
Highlights: Parkinson's disease impacts multiple facets of quality of life (QOL). Duration of illness is associated with worse QOL. Some facets of QOL, such as bodily discomfort and cognition are impacted early in the disease. Treatments to improve QOL may need to target different endpoints across the disease. Abstract: Health related quality of life (HRQoL) is negatively impacted in patients suffering from Parkinson's disease (PD). For the specific components that comprise HRQoL, the relationship between clinical variables, such as disease duration, is not fully characterized. In this cross-sectional study (n = 302), self-reported HRQoL on the Parkinson's Disease Questionnaire (PDQ-39) was evaluated as a global construct as well as individual subscale scores. HRQoL was compared in three groups: those within 5 years of diagnosis, those within 6–10 years of diagnosis, and those greater than 11 years since diagnosis. Non-parametric analyses revealed lower HRQoL with increasing disease duration when assessed as a global construct. However, when subscales were evaluated, difficulties with bodily discomfort and cognitive complaints were comparable in individuals in the 1–5 years and 6–10 year duration groups. Exploratory regression analyses suggested disease duration does explain unique variance in some subscales, even after controlling for Hoehn and Yahr stage and neuropsychiatric features. Our findings show that HRQoL domains in PD patients are affected differentially across the duration of the disease. Clinicians and researchers may need to tailor interventions intended to improve HRQoL at different domains as the disease progresses.